The Logan notebooks: poems - Lindenberg, Rebecca, author; The Center for Literary Publishing, Colorado State University, publisher (Colorado State University. Libraries, 2014)
Clouds, mountains, flowering trees. Difficult things. Things lost by being photographed. Things that have lost their power. Things found in a rural grocery store. These are some of the lists, poems, prose poems, and lyric anecdotes compiled in The Logan Notebooks, a remix and a reimagining of The Pillow Book of Sei Shonagon, a collection of intimate and imaginative observations about place-a real place, an interior landscape-and identity, at the intersection of the human with the world, and the language we have (and do not yet have) for perceiving it.--Provided by publisher.
Keywords: Poetry